Improved outcome of children with relapsed/refractory acute myeloid leukemia by addition of cladribine to re‐induction chemotherapy. (24th January 2021) - Ruan, Min; Liu, Li‐Peng; Zhang, Ao‐Li; Quan Qi, Ben; Liu, Fang; Liu, Tian‐Feng; Liu, Xiao‐Ming; Chen, Xiao‐Juan; Yang, Wen‐Yu; Guo, Ye; Zhang, Li; Zou, Yao; et al.
Abstract: Background: The preferred salvage treatment for children with relapsed/refractory acute myeloid leukemia (R/R‐AML) remains unclear. The combination of cladribine/Ara‐C/granulocyte‐colony stimulating factor and mitoxantrone (CLAG‐M) shown promising results in adult R/R‐AML. We aim to investigate the efficacy and safety of CLAG‐M versus mitoxantrone/etoposide/cytarabine (MEC) or idarubicin/etoposide/cytarabine (IEC) in R/R‐AML children. Methods: Fifty‐five R/R‐AML children were analyzed. The overall response rate (ORR), overall survival (OS), and progression‐free survival (PFS) at 3‐year were documented. Karyotype or mutations status were summarized as different risk groups. Results: The ORR was achieved in 80% (16/20) and 51% (18/35) of patients after one‐cycle of CLAG‐M and MEC/IEC treatment ( p < 0.001). The CLAG‐M group's OS (66.8% ± 16.2% vs. 40.4% ± 10.9%, p = 0.019) and PFS (52.6% ± 13.7% vs. 34.9% ± 9.1%, p = 0.036) at 3‐year was significantly higher than the MEC/IEC group. In high‐risk patients, 33.3% experienced progression of disease (PD) and 22.2% dead in CLAG‐M group, while 50% experienced PD and 43.8% dead in MEC/IEC. When it comes to low‐risk group, none of them in CLAG‐M experienced PD or death, while up to 50% of patients received MEC/IEC suffered PD, and all of them died eventually. Similar results were also found in the intermediate‐risk group. Surprisingly, the presence of FLT3‐ITD was associated with poor outcome in both groups. The most common adverse events were hematologic toxicities, and the incidence was similar in both group. Conclusions: CLAG‐M group demonstrated effective palliation along with acceptable toxicity in R/R‐AML patients. However, patients with FLT3‐ITD may benefit less from CLAG‐M, owing to higher PD rate and all‐cause mortality than other patients. Abstract : CLAG‐M regimen is a more valid option with similar adverse events as a salvage treatment for R/R‐AML in children when compared with conventional chemotherapy no matter in which risk group.